The Foreign Body Response. Issue 5 (May 2015) - Major, Melanie R.; Wong, Victor W.; Nelson, Emily R.; Longaker, Michael T.; Gurtner, Geoffrey C.
<x xml:space="preserve">Abstract</x> Background: The surgical implantation of materials and devices has dramatically increased over the past decade. This trend is expected to continue with the broadening application of biomaterials and rapid expansion of aging populations. One major factor that limits the potential of implantable materials and devices is the foreign body response, an immunologic reaction characterized by chronic inflammation, foreign body giant cell formation, and fibrotic capsule formation. Methods: The English literature on the foreign body response to implanted materials and devices is reviewed. Results: Fibrotic encapsulation can cause device malfunction and dramatically limit the function of an implanted medical device or material. Basic science studies suggest a role for immune and inflammatory pathways at the implant-host interface that drive the foreign body response. Current strategies that aim to modulate the host response and improve construct biocompatibility appear promising. Conclusions: This review article summarizes recent basic science, preclinical, and clinicopathologic studies examining the mechanisms driving the foreign body response, with particular focus on breast implants and synthetic meshes. Understanding these molecular and cellular mechanisms will be critical for achieving the full potential of implanted biomaterials to restore human tissues and organs.